Good reputation: A reputation for doing good - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
Having a good product is no longer sufficient for companies to retain a competitive edge in the modern society where consumers are getting more sophisticated and environmentally conscious. And corporations around the world are realising it. What is it that motivates companies to take up the corporate social responsibility flag and how does it relate to their corporate reputation?